Foreign economic activity of the Kabardino-Balkarian Republic in the second half of the 90s of the XX century - Marina V., Zhanokova (Kavkazologiya, 2024)
Since the mid-90s of the twentieth century, the authorities of the Kabardino-Balkarian Republic have increased overseas economic activity as a means of overcoming the economic crisis. The positive results of the activities of the authorities of the Kabardino-Balkarian Republic in this area were: the establishment of the Ministry of Foreign Relations of the Kabardino-Balkarian Repub-lic; the re-establishment of the Department of Foreign Economic Relations within it; the conclu-sion of interstate agreements with the Government of the Republic of Abkhazia, the Government of the Republic of Turkey and the Government of the Republic of Turkmenistan. Economic ties between the Kabardino-Balkarian Republic and the Commonwealth of Independent States began to develop. The number of joint Russian-foreign companies registered in the Kabardino-Balkarian Republic grew. Contracts were signed with large companies from Italy, Cyprus, Canada, France and China. Nevertheless, the success of joint ventures in the Kabardino-Balkarian Republic in the second half of the 1990s turned out to be insignificant, which was due to the strict federal tax and credit policies that hampered the development of production activities, the fall of the ruble ex-change rate and the military conflict in Chechnya, which caused a significant decrease in the in-vestment attractiveness of the Kabardino-Balkarian Republic and the entire North Caucasus at the international level.